Effects of Sn-Ag-x layers on the solderability and mechanical properties of Sn-58Bi solder. Issue 1 (4th March 2021) - Zhang, Shuang; Liu, Yang; Zhang, Hao; Zhou, Min; Xue, Yuxiong; Zeng, Xianghua; Cao, Rongxing; Chen, Penghui
ABSTRACT: Sn-Ag-x solders were used as the interfacial layers between SnBi solder and Cu substrate. The effects of Sn-Ag-x layers on the solderability, microstructure, and mechanical properties of SnBi solder joint were investigated. Experimental results indicate that all the barrier layers have positive effects on improving the wettability of SnBi solder. The relative area and grain size of β-Sn was enlarged due to the addition of Sn-Ag-x layers. Meanwhile, the addition of the interfacial layers decreased the hardness of the SnBi solder joint. The addition of Sn-Ag-x layers increased the thickness of the interfacial intermetallic compound (IMC) but had limited effects on the shear force of the SnBi solder joint. Due to the addition of the interfacial layers, the brittleness of the SnBi/Cu solder joints during the shear test was slightly suppressed.